230k views
5 votes
2. Match each set of equations with the move that turned the first

equation into the second.
6x + 9 = 4x - 3
2x + 9 =-3
Multiply both sides by 2
- 4(5x-7)=-18
5x - 7 = 4.5
Multiply both sides by-4
8 - 10x = 7+ 5x
4 - 10x = 3 + 5x
Multiply both sides by 1
x = 4
5x =- 16
Add to both sides
- 4x
12x + 4 = 20x + 24
Add to both sides
3x + 1 = 5x + 6
-il

2. Match each set of equations with the move that turned the first equation into the-example-1

1 Answer

3 votes

Answer:

Explanation:

1) In the first equation, - 4x was added to both sides of the equation. This is expressed as

6x - 4x + 9 = 4x - 4x - 3

2x + 9 = - 3

2) In the second equation, both sides of the equation was multiplied by - 1/4. This is expressed as

- 4 × - 1/4(5x - 7) = - 18 × - 1/4

5x - 7 = 4.5

3) In the third equation, - 4 was added to both sides of the equation. This is expressed as

8 - 10x = 7 + 5x

8 + (- 4) - 10x = 7 + (-4) + 5x

8 - 4 - 10x = 7 - 4 + 5x

4 - 10x = 5 + 5x

4) In the fourth equation, both sides of the equation was multiplied by - 4. This is expressed as

- 5x/4 × - 4 = 4 × - 4

5x = - 16

5) In the fourth equation, both sides of the equation was multiplied by 1/4x and 1/4. This is expressed as

12x × 1/4x + 4 × 1/4 = 20x × 1/4x + 24 × 1/4

3x + 1 = 5x + 6

User Chris Williams
by
4.9k points